ملاءمة الهياكل التنظيمية في الجامعات السعودية الناشئة لاستراتيجياتها في ضوء رؤية المملكة 2030: جامعة بيشة أنموذجا - العلياني، غرم الله بن دخيل الله سابر (جامعة طنطا - كلية التربية, 2022)
هدف البحث إلى الكشف عن ملاءمة الهيكل التنظيمي لجامعة بيشة لاستراتيجيتها في ضوء رؤية ٢٠٣٠، والتعرف على متطلبات تحقيق الملاءمة بين الهياكل التنظيمية في الجامعات الناشئة واستراتيجياتها في ضوء رؤية ٢٠٣٠ والكشف عن معوقات تحقيق الملاءمة بين الهياكل التنظيمية في الجامعات الناشئة في ضوء رؤية ٢٠٣٠، وتقديم تصور مقترح لتحقيق الملاءمة بين الهياكل التنظيمية للجامعات الناشئة واستراتيجياتها في ضوء رؤية ٢٠٣٠، واستخدم البحث المنهج الوصفي المكتبي، وتوصل البحث للعديد من النتائج منها، أهمية إعادة تنظيم الهياكل التنظيمية للجامعات الناشئة، واستحداث وكالات جديدة للجامعة لخدمة أهدافها الاستراتيجية، والاستفادة من التصور المقترح لتحقيق الملاءمة بين الهياكل التنظيمية للجامعات الناشئة واستراتيجياتها في ضوء رؤية ٢٠٣٠. The aim of the research is to reveal the suitability of the organizational structure of a university to its strategy in Vision 2030, and to identify the research requirements, the suitability between universities in the universities in Vision and their strategies in Vision 2030, and to reveal the obstacles to achieving suitability among emerging universities in Vision 2030, and to present a proposal for the suitability between the brands of emerging universities And its strategies in the light of the 2030 vision, and the research used the descriptive desk approach, and the research reached from the results from them, and then reorganized the structures of the emerging universities, and created new agencies for the university for its strategic goals, and benefited from the perception to reach the appropriateness between the university umbrellas for universities and their strategies in the light of the 2030 vision.
Keywords: التنمية المستدامة -- التعليم الجامعي -- الهياكل التنظيمية -- التخطيط الاستراتيجي -- الجامعات السعودية